Edward Said and the literary, social, and political world - Ghosh, Ranjan (Routledge studies in social and political thought ;, 2009)
The contributors to this volume - many among the foremost Edward Said scholars in the world - examine Said as the literary critic, his relationship to other major contemporary thinkers and his involvement with major movements of his time (such as music, feminism, new humanism, and Marxism).